Considering Photon Scattering and Harmonics for Synchrotron X-ray Radiographic Imaging of Polymer Electrolyte Membrane Fuel Cells. Issue 11 (24th May 2017) - Ge, Nan; George, Michael G.; Lee, Jongmin; Muirhead, Daniel; Chevalier, Stéphane; Banerjee, Rupak; Liu, Hang; Wysokinski, Tomasz W.; Belev, George; Webb, M. Adam; Zhu, Ning; Bazylak, Aimy
Abstract : We predicted the attenuated, undesired secondary scattered, and undesired harmonic components of measured X-ray intensities from synchrotron X-ray radiographic visualizations of liquid water in an operating polymer electrolyte membrane (PEM) fuel cell. The undesired secondary scattered component of the measured intensity increased as a function of the liquid water thickness (traversed by the X-ray beam). This increase in the secondary scattered component led to a decrease in the calibrated attenuation coefficient for liquid water, decreasing the accuracy of water quantification. We recommend calibrating the attenuated coefficient with a range of water thicknesses defined by the maximum expected water thickness present in the PEM fuel cell. The undesired harmonic component of the measured intensity also increased as a function of liquid water thickness, which led to a decrease in the accuracy of the measured liquid water thickness.